Evaluation of stress among undergraduate dental students in Al-Qadisiyah University-Iraq - Murad, Ali H.; Alhajj, Mohammed N. (Journal of Stomatology, 2017)
Aim of the study. To explore the self-reported source of stress among dental students and to identify the role of gender, marital status, and study level on the perceived stressors. Materials and methods. A modified self-reported questionnaire was completed by undergraduate dental students registered at Al- Qadisiyah University, College of Dentistry. The questionnaire consisting of 41 close-ended questions was divided into seven domains. Stress was assessed in a response to four items. The collected data were analyzed for frequencies, means, and comparisons between the study participants in relation to the gender, marital status, and study levels. Nonparametric tests were used with confidence interval 95% (α error = 0.05). Results. A total of 185 dental students with mean age of 19.86±1.40 years completed the questionnaire. There was a prevalence of females (1.4:1) and single students rather than married ones. The “workload” domain was the highest stressor domain while the “social stressors” domain was the lowest. Among the stressor questions, the most stressor factor was “examinations and quizzes” while the least stressor was “difficulty of class work”. Comparison between the participants revealed more concern in females, married, and pre-doctoral students in most of the stress-provoking factors. Conclusion. Considerable levels of stress were observed among dental students. The study also identified stressors affecting the students’ academic life. It is important to include stress management programs in the curriculum of the dental college.